Effect of electrolysis treatment on the biomineralization capacities of pearl oyster Pinctada margaritifera juveniles. (5th December 2016) - Latchere, Oïhana; Fievet, Julie; Lo, Cédrik; Schneider, Denis; Dieu, Stéphanie; Cabral, Philippe; Belliard, Corinne; Ky, Chin-Long; Gueguen, Yannick; Saulnier, Denis
Abstract: The present study investigated the effect of electrolysis on the biomineralization capacities of juveniles of the mollusk Pinctada margaritifera for the first time. Size-selected individuals from two groups, "Medium" and "Large", from a multi-parental family produced in a hatchery system were subjected to electrolysis under a low voltage current over a nine-week experimental period. The growth of the juveniles was individually monitored and assessed weekly by wet weight and shell height measurements. At the end of the experiment, mantle tissue was sampled for biomineralization-related gene expression analysis. Electrolysis significantly increased pearl oyster growth in terms of shell height and wet weight for Large juveniles from the 5th and the 2nd week, respectively, until the end of the experiment. However, differences were only significant for Medium individuals from the 7th week for shell height and from the 9th week for wet weight. Furthermore, transcriptional analysis of six known biomineralization genes coding for shell matrix proteins of calcitic prisms and/or nacreous shell structures revealed that five were significantly overexpressed in the mantle mineralizing tissue under electrolysis: three in common between the two size class groups and two that were expressed exclusively in one or the other group. Finally, we found no statistical difference of the shell thickness ratio between individuals undergoing electrolysis and control conditions. Taken together, our results indicate, for the first time in a calcifying marine organism, that electrolysis influences molecular mechanisms involved in biomineralization and may stimulate some parameters of pearl oyster growth rate. Graphical abstract: Highlights: Electrolysis may increase some growth rate parameters in juvenile pearl oysters. Expression levels of some biomineralization-related genes are enhanced by electrolysis. No effect of electrolysis was recorded on shell thickness of juvenile pearl oysters.